Politik Luar Negeri Australia terhadap Indonesia di Bawah Pemerintahan Perdana Menteri Kevin Rudd - , YULIA TRIANAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Derived from either party who led Australia ,bilateral relations with Indonesia in foreign policy will always be seen as important for Australia. Approaches and priorities will change with changes that occur in the body of government and relevant actors at the executive level. And Indonesia is a country that is seen as the closest neighbors, where the threat to Australia comes. In 2007 Kevin Rudd ( Australian Labor Party ) officially became Prime Minister of Australia, replaced John Howard of the Liberal Party. There are significant differences in the priority emphasis on foreign policy and leadership style that captured both the Prime Minister. Especially regarding foreign policy towards Indonesia. Foreign policy towards Indonesia under Kevin Rudd, attempts to run out comprehensive cooperation that existed during the reign of the Labour Party in the past. under the Labor Government, the Australia- Indonesia relationship more stable, not much tension as when the ruling Liberal Party. Policy differences in foreign policy between the Kevin Rudd and Howard Governmentâs, because there are differences in individual preferences in viewing the position of Indonesia as a strategic partner, driven by political interests represented in the leadership characteristics and differences in party ideology where they came from, as well as the effect of changes in the external environment of Australia. The differences is seen in the accomplishments of defence policy, economic and social cooperation between the two governments. Kevin Rudd runs the political pillar of foreign policy through a comprehensive Engagement with neighbors, but also would not take for granted its alliance with the United States to secure the region, it's just that Australia will be more independent in determining its security policy.